Quiste maxilar de la línea media. Reporte de un caso - León Arcila, Miguel Evelio (Revista Estomatología, 2002)
Cyst is defined as a pathological cavity of epithelium thai contains material liquid or semisolid. The cyst of the mean Une is a bone cyst that is form in the mean cleavage of the palate by embryonic remains. It is presented a clinical case of a patient of 38 years old to whom during a routine denial examinations, his dental doctor finds a cyst located in the alveolar curbing vestibular zone between teeth 11 and 21. Show a bony destruction of approximately 2 cm of diameter, with involvement of the external and internal. Cortical plates It was accomplished a presumptive diagnosis of a cyst of the mean line, the one which was confirmed by a puntion biopsy. It was performed a surgical procedure to resect the cyst with primary bony reconstruction. Histopatologic analysis confirmed the diagnosis, postoperatoria patient evolution was satisfactory, and show the control 2-year offer curgery.